2020
DOI: 10.1038/s41598-020-72628-w
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents exhibit reduced Pavlovian biases on instrumental learning

Abstract: Multiple learning systems allow individuals to flexibly respond to opportunities and challenges present in the environment. An evolutionarily conserved “Pavlovian” learning mechanism couples valence and action, promoting a tendency to approach cues associated with reward and to inhibit action in the face of anticipated punishment. Although this default response system may be adaptive, these hard-wired reactions can hinder the ability to learn flexible “instrumental” actions in pursuit of a goal. Such constrain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 116 publications
(143 reference statements)
6
48
3
Order By: Relevance
“…Research has shown that people dynamically adjust their response threshold in both decision-making tasks [ 56 ] and cognitive control tasks [ 30 , 57 ] as they learn to expect greater rewards. It remains to be tested how these cognitive control adjustments are distributed across both threshold and drift rate with changes in both reward and punishment, as well as with individual-specific [ 58 , 59 ] and context-specific [ 60 ] differences in learning from these positive and negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that people dynamically adjust their response threshold in both decision-making tasks [ 56 ] and cognitive control tasks [ 30 , 57 ] as they learn to expect greater rewards. It remains to be tested how these cognitive control adjustments are distributed across both threshold and drift rate with changes in both reward and punishment, as well as with individual-specific [ 58 , 59 ] and context-specific [ 60 ] differences in learning from these positive and negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, adolescents are more sensitive to the effects of social stress, such as social isolation, on mental health, and are more capable of recovering from those same social stressors compared to children and adults ( Fuhrmann et al 2015 ). Recent work suggests that adolescents, more so than children or adults, rely on learning strategies that are specifically suited to exploring novel opportunities and challenges in the environment ( Raab and Hartley 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that people dynamically adjust their response threshold in both decision-making tasks [56] and cognitive control tasks [30,57] as they learn to expect greater rewards. It remains to be tested how these cognitive control adjustments are distributed across both threshold and drift rate with changes in both reward and punishment, as well as with individualspecific [58,59] and context-specific [60] differences in learning from these positive and negative outcomes.…”
mentioning
confidence: 99%